Study of carotinoids of Momordica harantia - Burlaka, Iryna; Korol, Viktoriia; Popyk, Andriy; Miroshnychenko, Olha (Annals of Mechnikov's Institute, 2023)
Introduction. Carotenoids are one of the most promising groups of dietary supplements. The human body is incapable of synthesizing these compounds. Therefore, the search for new, valuable raw materials in Ukraine with the aim of developing dietary supplements, functional food products, and active pharmaceutical ingredients on its basis remains relevant. It can be used to create domestic targeted medicines or products with a predictable physiological effect. These products will have a health-improving effect on the human body and will be able to provide prevention and treatment of a number of diseases. Traditional sources of carotenoids and medicines based on them are sea buckthorn fresh fruits, rose hips fruits, tomatoes, carrots root crops, pumpkin fruit pulp, calendula flowers, etc. This list is constantly expanding due to new species. Momordica charantia L. (Indian cucumber, bitter gourd, bitter melon) is an annual vine of the pumpkin family (Cucurbitaceae). It is a vegetable and medicinal plant from Southeast Asia that grows well in Kharkiv, Poltava, etc. regions of Ukraine. This plant exhibits various biological, medicinal and pharmacological functions, namely: anthelmintic, antifertility, antimalarial, laxative, hypoglycemic, antimutagenic, antiulcer, antilipolytic, hepatoprotective, antitumor, antiviral, antibacterial, etc. Analysis of literature data showed that bitter melon contains various groups of biologically active compounds (BACs): triterpenoids, peptides, essential and fatty oils, a complex of phenolic compounds, carotenoids, alkaloids, etc. However, information about research into the phytochemical composition of plants cultivated in Ukraine is very limited. That is why the study of ALS groups, namely the carotenoids of Charantia momordica, is relevant. The aim of this research was to study the qualitative composition and determine the quantitative content of carotenoids in the fruits and seeds of Momordica Harantia. Material & methods. The objects of the study is the fresh, mature green fruits and seeds of the Momordica charantia L. They were harvested in the Poltava region in 2021. The dried raw materials were crushed using an electric grinder. The method of thin-layer chromatography (TLC) was used in accordance with the State Pharmacopoeia of Ukraine (SPhU) monograph to identify the carotenoids of Momordica charantia L. fruits and seeds. While their identification was carried out by the values of the mobility coefficients (Rf). Sample preparation for obtaining carotenoids from the studied raw materials for TLC analysis was carried out under cooling and in the shade to avoid oxidation, prevention of photoisomerization, destruction of carotenoids. About 2.0 g of the crushed raw material was placed in a 100 ml conical flask with a ground stopper, 25 ml of hexane was added and extracted at room temperature with periodic shaking for 1 hour. The resulting extract was filtered, concentrated and used to detect carotenoids on Sorbfil plates in an ascending manner. Chromatography conditions: chromatographic plates "Sorbfil, PTSH-P-A". size 10x15 cm. Results & discussion. Carotenoids were identified by TLC method. Analytical signals of the identification reactions indicated the presence of carotenoids in the fruits and seeds of Momordica charantia L.. Since the separation of pigments was better in mobile phase 3, the results of chromatography in it were taken as a basis. The studied samples contained 4 zones of yellow-brown color on a white background, which were assigned to the class of carotenoids. Then the chromatograms were treated with a 10% solution of phosphoric-molybdic acid in ethanol. After heating the plate at a temperature of 60-80 °C, carotenoids appeared in the form of blue spots on a yellow-green background. The relative speed of movement of one of them coincided with the Rf value of β-carotene, and the others corresponded to the data of the literature and they were identified as lutein (0.373), β-cryptoxanthin (0.612), lycopene (0.802) and β-carotene (0.973). Lycopene was also found to be the dominant carotenoid in the seeds and β-carotene in the fruits. The carotenoids content of the Momordica charantia L. fruits was 10.21±0.01 mg/%, calculated on β-carotene, in Momordica charantia L. seeds - 9.13±0.02%, calculated on lycopene. Conclusions. It is the first time, a study of the carotenoid complex of the Momordica charantia L. fruits and seeds was carried out. The presence of lutein, β-cryptoxanthin, lycopene and β-carotene was determined by the TLC method. Lycopene was also found to be the dominant carotenoid in the seeds and β-carotene in the fruits. The content of carotenoids in the Momordica charantia L. fruits was 10.21±0.01 mg/%, in terms of β-carotene, in seeds - 9.13±0.02%, in terms of lycopene. These data indicate the possibility of using the studied raw materials for the manufacture of medicinal products and functional food products. Keywords: Momordica charantia L. seeds, Momordica charantia L. fruits, carotenoids, thin-layer chromatography (TLC).